Duck TRIM29 negatively regulates type I IFN production by targeting MAVS - Li, Weiqiang; Song, Yating; Du, Yuqing; Huang, Zhanhong; Zhang, Meng; Chen, Zuxian; He, Zhuoliang; Ding, Yangbao; Zhang, Junsheng; Zhao, Luxiang; Sun, Hailiang; Jiao, Peirong (Frontiers in Immunology, 2023)
The innate immune response is a host defense mechanism that induces type I interferon and proinflammatory cytokines. Tripartite motif (TRIM) family proteins have recently emerged as pivotal regulators of type I interferon production in mammals. Here, we first identified duck TRIM29, which encodes 571 amino acids and shows high sequence homology with other bird TRIM29 proteins. DuTRIM29 inhibited IFN-β and IRF7 promoter activation in a dose-dependent manner and downregulated the mRNA expression of IFN-β, IRF7, Mx and IL-6 mediated by duRIG-I. Moreover, duTRIM29 interacted and colocalized with duMAVS in the cytoplasm. DuTRIM29 interacted with duMAVS via its C-terminal domains. In addition, duTRIM29 inhibited IFN-β and IRF7 promoter activation and significantly downregulated IFN-β and immune-related gene expression mediated by duMAVS in ducks. Furthermore, duTRIM29 induced K29-linked polyubiquitination and degradation of duMAVS to suppress the expression of IFN-β. Overall, our results demonstrate that duTRIM29 negatively regulates type I IFN production by targeting duMAVS in ducks. This study will contribute to a better understanding of the molecular mechanism regulating the innate immune response by TRIM proteins in ducks.